PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) DAN PENYULUHAN PHBS SEBAGAI UPAYA PENINGKATAN KESEHATAN MASYARAKAT DI KELURAHAN KADIA KECAMATAN KADIA KOTA KENDARI - Jafriati Jafriati; Asnia Zainuddin; Nani Yuniar; Fifi Nirmala; Harleli Harleli; Syawal Kamiluddin Saptaputra (Universitas Halu Oleo, 2023)
Thematic Real Work Lecture (KKN) is a program held every year at Haluoleo Kendari University. One of the UHO Thematic KKN was held in Kadia Village, Kadia District, Kendari City with the title KKN